Targeting epigenetic and post-translational modifications regulating pyroptosis for the treatment of inflammatory diseases - Ri-Wen; Yu-Hang Yang; Tie-Ning Zhang; Chun-Feng Liu; Ni Yang (Elsevier, 2024)
Inflammatory diseases, including infectious diseases, diabetes-related diseases, arthritis-related diseases, neurological diseases, digestive diseases, and tumor, continue to threaten human health and impose a significant financial burden despite advancements in clinical treatment. Pyroptosis, a pro-inflammatory programmed cell death pathway, plays an important role in the regulation of inflammation. Moderate pyroptosis contributes to the activation of native immunity, whereas excessive pyroptosis is associated with the occurrence and progression of inflammation. Pyroptosis is complicated and tightly controlled by various factors. Accumulating evidence has confirmed that epigenetic modifications and post-translational modifications (PTMs) play vital roles in the regulation of pyroptosis. Epigenetic modifications, which include DNA methylation and histone modifications (such as methylation and acetylation), and post-translational modifications (such as ubiquitination, phosphorylation, and acetylation) precisely manipulate gene expression and protein functions at the transcriptional and post-translational levels, respectively. In this review, we summarize the major pathways of pyroptosis and focus on the regulatory roles and mechanisms of epigenetic and post-translational modifications of pyroptotic components. We also illustrate these within pyroptosis-associated inflammatory diseases. In addition, we discuss the effects of novel therapeutic strategies targeting epigenetic and post-translational modifications on pyroptosis, and provide prospective insight into the regulation of pyroptosis for the treatment of inflammatory diseases.